Ultrasonic study and physical properties of borotellurite glasses - Mohamed Kamari, Halimah; Ab. Aziz, Sidek; Wan Yusoff, Wan Mohamad Daud; Hassan, Zainul Abidin; Talib, Zainal Abidin; Abdul Wahab, Zaidan; Sulaiman, Zainal Abidin; Hashim, Mansor (Science Publications, 2005)
A series of glasses (TeO2)x (B2O3)1-x with x = 0.6, 0.63, 0.65, 0.70, 0.73, 0.75, 0.78 and 0.80 were synthesized by rapid quenching. Longitudinal and shear ultrasonic velocity were measured at room temperature and at 5 MHz frequency. Elastic properties, Poisson’s ratio and micro hardness have been calculated from the measured density and ultrasonic velocity at room temperature. Estimated parameters based on Makishima-Mackenzie theory and bond compression model were calculated in order to analyze the experimental elastic moduli. Comparison between the experimental elastic moduli data obtained in the study and the calculated theoretically by other models has been discussed.